2020
DOI: 10.1111/bjdp.12360
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' well‐being: The role of basic needs fulfilment in family context

Abstract: Although there is an increasing interest in studying the relations between the satisfaction of basic psychological needs and well‐being, this association for both parents and adolescents has been to some extent disregarded within the self‐determination theory. The present study was aimed at testing a model of relations between father, mother, and adolescent’s perception of basic needs fulfilment and well‐being. Participants were 98 co‐living family units of mother, father, and adolescents (54% males) aged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We thus expected to find associations between some of the basic need satisfactions of parents and adolescents. However, while our correlational analysis basically replicated the significant positive correlations between parents' and adolescents' BPNS (see Tables 2 and 4) found in the literature (e.g., Lo Cricchio et al, 2021;Nishimura et al, 2021), results from our two longitudinal analyses did not detect such influence over time. More specifically, parents' need satisfaction did not reliably predict adolescents' need satisfaction (no parental need effect) and adolescents' need satisfaction did not predict parents' need satisfaction (no child's needs effect).…”
Section: Associations Between Parents' and Adolescents' Needssupporting
confidence: 88%
See 3 more Smart Citations
“…We thus expected to find associations between some of the basic need satisfactions of parents and adolescents. However, while our correlational analysis basically replicated the significant positive correlations between parents' and adolescents' BPNS (see Tables 2 and 4) found in the literature (e.g., Lo Cricchio et al, 2021;Nishimura et al, 2021), results from our two longitudinal analyses did not detect such influence over time. More specifically, parents' need satisfaction did not reliably predict adolescents' need satisfaction (no parental need effect) and adolescents' need satisfaction did not predict parents' need satisfaction (no child's needs effect).…”
Section: Associations Between Parents' and Adolescents' Needssupporting
confidence: 88%
“…While the satisfaction of basic psychological needs is posited to occur in social relationships, studies on BPNS transmission in parent-child relationships are still lacking. Only a small number of studies on BPNS in parents and children exists (e.g., Lo Cricchio et al, 2021;Nishimura et al, 2021), but most of them are cross-sectional, examine basic needs as one concept, and do not assess parents' perception of their child's need satisfaction. Our first exploratory study and our second preregistered confirmatory study aimed to respond to these limitations to better understand the interplay of basic psychological needs between parents and adolescents over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental study among Belgian mother-adolescent dyads showed that the self-reported BPNS of adolescents and mothers were positively and moderately correlated during a recorded conversation (Wuyts et al, 2018). Other cross-sectional studies among Italian (Costa et al, 2019;Lo Cricchio et al, 2021) and Japanese (Nishimura et al, 2021) parents and adolescents reported moderate positive associations between parents' and adolescents' overall BPNS.…”
Section: Introductionmentioning
confidence: 96%